Clinical commissioning of the INCISE™ multileaf collimator for cyberknife M6™ system. (September 2016) - Kaissi, Tarek El; Torfeh, Tarraf; Shulman, Adam; Hammoud, Rabih; Al-Hammadi, Noora
Abstract : Introduction: The National Center for Cancer Care and Research (NCCCR) at Hamad Medical Corporation in Qatar is amongst the first institutions in Asia and Europe to have the CyberKnife® M6 FIM system (Accuray, Inc., Sunnyvale, CA, USA) including Fixed Collimators, Iris Variable Aperture Collimator and InCise™ Multileaf Collimator. Purpose: To report our commissioning experiences of the CyberKnife M6 InCise™ Multileaf Collimator system. Materials and methods: Accuray guidelines were used to conduct measurements. A detailed description of the equipment used, the mechanical alignment, the verification procedures, and the alignment of the detector motion with the radiation beam is described. Incise MLC testing was conducted as per Accuray procedure. Further MLC tests were developed to verify its feasibility under certain clinical settings. Results: Our results were within the manufacturer specifications. Results for both the Sun Nuclear Edge detector and PTW SRS diode 60018 were found to be comparable. Measurement conditions specified by Accuray were sufficient; however the use of a reference chamber introduced additional noise for the continuous profile acquisitions. As compared to fixed and IRIS collimators, the incise MLC produced acceptable results with an average of 20% decrease in treatment delivery time. Conclusions: Our results are amongst the first set of data reported on the InCise™ MLC and were within the manufacturer specifications. These results will be used to develop a benchmark reference for periodic Quality Control (QC). Disclosure: Authors have nothing to disclose.